Relationship Between Early Detection Of Signs And Symptoms Of Hypoglycemia With Hypoglycemia Prevention Behavior In Patients With Diabetes Mellitus Type II At Yosowilangun Community Health Center - Febrianti, Ainin Nurohmah; Abidin, Zainal; Yunita, Rizka (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2024)
Diabetes mellitus is a metabolic disorder characterized by high blood sugar levels associated with abnormal carbohydrate, fat, and protein metabolism caused by decreased insulin secretion or decreased insulin sensitivity effectively. One of the acute complications in patients with Diabetes Mellitus (DM) 2 is hypoglycemia. Hypoglycemia is a blood glucose level ≤ 70 mg / dl (3.9 mmol / L). The purpose of this study was to determine the correlation between early detection of signs and symptoms of hypoglycemia and hypoglycemia prevention behavior in patients with type II diabetes mellitus at the Yosowilangun Health Center.This study design was descriptive analytical using a cross-sectional method. All patients with type II diabetes mellitus at the Yosowilangun Health Center. This study used a purposive sampling technique. The Amount population is 50 patient. The research sample was 48 respondents. The instrument used for data collection using a questionnaire for early detection of signs and symptoms and prevention of hypoglycemia. Both instruments were categorized as good, sufficient, and lacking. The statistical test used Spearmen-rank with a significance level of 0.05.The results of the study showed that early detection of signs and symptoms of hypoglycemia was sufficient (66.7%) and prevention of hypoglycemia was sufficient (44.8%). The results of data analysis using the Spearmen-rank test showed that the p value was smaller than significant (0.001 <0.05), so there was a correlation between early detection of signs and symptoms of hypoglycemia and prevention of hypoglycemia in Type 2 DM patients at the Yosowilangun Health Center. The results of this study can be concluded that Type 2 DM respondents with a history of hypoglycemia can prevent hypoglycemia through knowledge of the signs and symptoms of hypoglycemia, so that they can minimize recurrent hypoglycemia. This can be recommended for health services that early detection of the disease as a guideline in treating Type 2 DM patients with hypoglycemia